Az uniós csatlakozás támogatottságának változásai Horvátországban - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2012)
In this short paper, I shall attempt to throw light on the growth of euroscepticism in Croatian public opinion, analysing particularly the dynamics of support for Croatia’s joining the EU, and trust in the EU. Since mid-2003 there have been considerable changes in the attitudes of Croatian citizens to accession to the EU. According to public opinion polls of mid-2003, about three quarters of Croatian citizens supported Croatian accession, after which, from the autumn of the same year, the process of a decline in support began, the sudden fall of public support for Croatian accession to the EU of some 30–40% happened and lasts till now. The key findings were based on Standard Eurobarometer surveys from 2004 till now, as well as the Croatian public opinion polls. The aim of the paper is to analyse characteristics of euroscepticism in Croatia, defined as a combination of distrust in the European Union and distaste for membership. The main reasons for such low public support for EU membership are the negative assessment of the conditions offered, and scepticism about the potential benefits that accession to the EU would bring Croatia. There are via economic fears such as the rise in the price of real estate as a result of demand from foreign purchasers, the import of cheaper agricultural products, the obliteration of indigenous products. The purpose of this paper is to analyse negative trends appearing not only from the Croatian side, but also form the EU and to emphasize the complexity of the situation.